Streamlining Climate Education to Tackle Climate Crisis: Call For Action to Empower Ethiopia’s Next Generation with Climate Knowledge and Build Resilience - Belay, Berhanu; Ambaw, Gebermedihin; Makonnen, Brook T.; Amha, Yosef; Demissie, Teferi Dejene; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate change has become a reality that requires mitigation and adaptation of climate change by devising appropriate measures and participatory approaches. Ethiopia is committed to setting policy frameworks and implementation strategies to mitigate and adapt to climate change and produce a climate change-resilient society. It is well understood that education and climate change have a reciprocal relationship, and education has a strong power for climate change adaptation and mitigation endeavours. Formal and formal education at each stage, from kindergarten to higher learning institutions, contributes to the effort to produce a climate-resilient and climate-literate society. In particular, Universities have a tremendous role in climate change mitigation and adaptation by devising climate-sensitive curricula and capable staff development for teaching climate sciences, conducting climate research, and enhancing climate-oriented community engagement and policy advice based on the research results. In this premise, accelerating the impact of CGIAR climate research in Africa (AICCRA) approached MoE and universities. It created partnerships to galvanize the integration of climate education into university curricula and programs. Various consultations and workshops were conducted to devise a participatory climate education integration approach in Ethiopian public universities through demand-driven gap analyses. The gap analyses have culminated by producing policy briefs that have also suggested recommendations. The policy brief was submitted to the Ministry of Education. The gap analyses of the freshmen curricula and climate discipline-oriented courses offered in Universities have gaps in capturing contemporary climate knowledge products. The policy brief also demonstrated that, Ethiopia's educational strategic roadmap omitted the crucial "Climate Basics" course, leaving a significant knowledge gap among its students. The policy brief suggested that Ethiopian Universities should install climate basics in freshmen programs as a common and compulsory course through the participation of key stakeholders. A one-day workshop was conducted by engaging multiple stakeholders on September 25, 2023, to install climate basics in freshmen curricula as a compulsory course. More than 60 professionals representing different organizations participated in the workshop. Presentations were made to know the interests and aspirations of professionals/institutions representing different climate-sensitive intuitions, including the Ministry of Education, Ministry of Agriculture, Ministry of Planning and Development, Ethiopian Metrology Institute, Agricultural Transformation Institute, Disaster Risk Management Institute, Universities, UNESCO, EPA, and ILRI-AICCRA. The Presentations in one accord have recommended the integration of climate Basics in the freshman program as a compulsory and credited course. The interactive workshop demonstrated Ethiopia's decision to prioritize climate education as a testament to its commitment to tackling the climate crisis head-on. By equipping its future generations with the knowledge and tools to address climate-related challenges, Ethiopia is poised to become a regional and continental leader in building a climate-resilient future. It was noted from the workshop that the implementation strategies need to be devised by engaging conference organizers as lead actors. As per the recommendations of the workshop participants, MoE, UNESCO, EPA, and AICCRA should discuss and persuade the government to implement the recommendations by scanning opportunities and Ministry of Education programs in making our curricula dynamic and appropriate to the changing global world and contribute Ethiopia’s commitment to implement climate resilient and green economy.